Spatial and temporal analysis of postural control in children with high functioning Autism Spectrum Disorder. (August 2017) - Goulème, Nathalie; Scheid, Isabelle; Peyre, Hugo; Maruani, Anna; Clarke, Julia; Delorme, Richard; Bucci, Maria Pia
Highlights: ASD children showed poor postural stability with respect to control children as well as in spatial and in temporal analysis of the CoP deplacement. ASD children could have impairment in the cerebellar integration. ASD children could have an inappropriate use of sensory input namely visuovestibular to maintain their postural stability according to a deficit in cerebellar integration. Abstract: Background: Children with autism spectrum disorders (ASD) have poor postural stability. The objective of our study was to explore further postural capabilities in ASD children by measuring spatial as well as temporal displacement of the center of pressure using wavelet analysis. Method: Thirty children with ASD (12.1 ± 2.9 years) and 30 sex-, age- and IQ-matched typically developing children participated in the study. We recorded postural control using Multitest, also called Balance Quest, Equilibre from Framiral ® in three viewing conditions (eyes open, eyes closed and with perturbed vision) and in two postural conditions (stable and unstable). Results: Our results show that children with ASD displayed a deficit in postural stability in comparison with typically developing children, especially when sensory inputs are not all available. Conclusion: Such poor postural control in children with ASD could be due to both an impairment in using sensorial inputs appropriately and a deficit in the ability to compensate for sensorial changes.